2018
DOI: 10.1177/0284185118799519
|View full text |Cite|
|
Sign up to set email alerts
|

ALBI and P-ALBI grade in Child-Pugh A patients treated with drug eluting embolic chemoembolization for hepatocellular carcinoma

Abstract: Background Treatment outcome for hepatocellular carcinoma (HCC) is related to tumor burden and liver function. Grading systems assessing liver function need validation in different clinical settings. Purpose To evaluate drug-eluting embolic transarterial chemoembolization (DEE-TACE) in Child-Pugh A HCC with respect to albumin-bilirubin (ALBI) and platelet-albumin-bilirubin (P-ALBI) grade. Material and Methods Forty-nine patients with Child-Pugh class A, diagnosed with HCC and allocated to DEE-TACE treatment, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 197 publications
1
12
0
Order By: Relevance
“…A risk of post hepatectomy liver failure and long-term survival is stratified using the simple score [27]. It has a long-term impact on liver function on curative or locoregional therapy for hepatocellular carcinoma [28,29,30,31]. The present data also aligned with results from a previous study involving 63 Chinese PBC patients proving that a smaller ALBI score predicted improved event-free survival [32].…”
Section: Discussionsupporting
confidence: 80%
“…A risk of post hepatectomy liver failure and long-term survival is stratified using the simple score [27]. It has a long-term impact on liver function on curative or locoregional therapy for hepatocellular carcinoma [28,29,30,31]. The present data also aligned with results from a previous study involving 63 Chinese PBC patients proving that a smaller ALBI score predicted improved event-free survival [32].…”
Section: Discussionsupporting
confidence: 80%
“…The preoperative ALBI score has a long‐term impact on liver function after curative therapy for HCC . Accumulating evidence indicated that the ALBI score predicted prognosis of patients with HCC who underwent oral chemotherapy using sorafenib, radioembolization, and drug‐eluting embolic chemoembolization . The ALBI score also correlated with recurrence of HCC after curative treatments, surgical resection, or ablative therapy .…”
Section: Discussionmentioning
confidence: 99%
“…This advantage can be exemplified considering that using mHAP-II, a patient with an HCC of 20 cm and albumin 2.1 mg/dL would have received the same points as a patient with a tumor of 6 cm and 3.5 mg/dL albumin. ALBI and pALBI are 2 scores proposed to overcome the limitations of the CPT score in assessing liver function [13, 14, 23]. In CPT class A, ALBI succeeded in distinguishing 2 prognostic subgroups, ALBI grade 1 and ALBI grade 2, with a 10-month difference in survival.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Pinato et al [18] validated the prognostic role of the ALBI grade across all BCLC stages. In pALBI, platelet count was added to include a surrogate marker of portal hypertension, and this prognostic model was proposed for CPT-A patients undergoing TACE [23]. However, these 2 scores did not perform very well in our TACE series, and the reason for this poor performance could rely on the fact that most (nearly 80%) of our patients belonged to ALBI grade 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation